The Influence of Product Quality and Price on Galvalum Purchasing Decisions - Ajisaputra, Iswal Romdanu; Sudjiono, Sudjiono; Yap, Nonni (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
The research ascertain the impact of product pricing and quality on the purchasing decision galvalum at the Sumber Rejeki Shop, Tanjunganom Nganjuk District, partially and simultaneously, and to analyze the influence of the dominant variables on the decision to purchase galvalum at the Sumber Rejeki Shop, Tanjunganom Nganjuk District. This type of research uses a quantitative. This research used a sample of 96 respondents. Sampling used a nonprobability sampling technique with the Accidental Sampling method. The test used is data analysis using SPSS 25, in this research using a questionnaire or questionnaire and Multiple linear regression analysis is employed. Based on the outcomes of test it can be concluded that partially, Product Quality (X1) and Product Price (X2) partially have a positive and significant effect on the decision to purchase galvalum at the Sumber Rejeki Shop, Tanjunganom Nganjuk District. Product quality (X1) and product price (X2) simultaneously have a positive and significant effect on the decision to purchase galvalum at the Sumber Rejeki Shop, Tanjunganom Nganjuk District. The Product Price Variable (X2) is more dominant in influencing the decision to purchase galvalum at the Sumber Rejeki Store, Tanjunganom Nganjuk District than the Product Quality Variable. Keywords: Product cost, product quality, and purchasing choices